Modification Targeting the “Rana Box” Motif of a Novel Nigrocin Peptide From Hylarana latouchii Enhances and Broadens Its Potency Against Multiple Bacteria - Bao, Kaifan; Yuan, Weiyuan; Ma, Chengbang; Yu, Xi; Wang, Lei; Hong, Min; Xi, Xinping; Zhou, Mei; Chen, Tianbao (Frontiers in Microbiology, 2018)
Public health is confronting threat by antibiotic resistance nowadays, and it urges us to develop new antibacterial strategies. Antimicrobial peptides (AMPs) have been considered as promising therapeutic candidates against infection in the post-antibiotic era. In this paper, nigrocin-HL was identified from skin secretion of Hylarana latouchii, and by substituting the “Rana box” sequence with a phenylalanine residue and C-terminus amidating, a shorter AMP nigrocin-HLM was obtained. Activities and toxicities of these two peptides in vitro and in vivo were compared. As a result, nigrocin-HLM not only displayed significantly increased potency against several representative microbes, but also high activity against the antibiotic-resistant methicillin-resistant S. aureus (MRSA, NCTC 12493 and ATCC43300 and several clinical isolates) as evidenced by markedly reduced minimal inhibitory concentration (MIC), minimal bactericidal concentration (MBC) and minimum biofilm eradication concentration (MBEC). More strikingly, nigrocin-HLM exhibited prominent inhibition against MRSA infection in a pneumonia mice model. In addition, the substitution attenuated the toxicity of nigrocin-HLM as evidenced by precipitously decreased hemolytic and cytotoxic activities in vitro, and acute toxicity to mice in vivo. Taken these results into consideration, nigrocin-HLM should be a promising therapeutic candidate for anti-infection. And in addition to dismiss an indispensable role of “Rana box” in maintaining antimicrobial activity of nigrocins, our data provided an inspired strategy for peptide optimization.